How does collaborative inventory management make progress? - Simatupang, Togar Mangihut (SBM ITB, 2003)
Collaborative inventory management (CIM) has revolutionized electronics, textile, apparel, and grocery industries. An intriguing question is how far does the movement of CIM challenge the traditional practice of inventory management? This paper illustrates how to expose and challenge flawed assumptions of traditional inventory management. It also proposes a collaborative replenishment process that consists of a cyclic process of tactical planning, execution, and control. The proposed scheme makes it possible for the chain members to apply collaborative inventory management. The paper also outlines directions for future research.Keywords:Â inventory management, supply chain collaboration, logistics, theory of constraints